Effect of high pressure processing and vacuum packaging on the preservation of fresh-cut peaches - Denoya, Gabriela Inés; Vaudagna, Sergio Ramon; Polenta, Gustavo Alberto (2018)
Nowadays consumers demand fresh-cut fruits free from additives and with appealing appearance. High pressure processing (HPP) could be a suitable alternative to preserve fresh-cut fruit, since it is less aggressive than thermal treatments. This work was accomplished to study the effect of HPP in combination with vacuum packaging (VP) on the preservation of fresh-cut peaches. Cubes of peaches were treated with a solution of ascorbic acid and citric acid to inhibit enzymatic browning and then subjected to: A) VP + HPP (500 MPa-5 min), B) only VP and C) Control. Immediately after processing, after 15 and 21 days, different evaluations were carried out over the samples: chromatic parameters (CIE L∗C∗h°), polyphenoloxidase (PPO) activity, Textural Profile Analysis, and ethanol content. During the period evaluated, L∗ and C∗ were significantly lower in vacuum-packed and pressurized samples than in the control. At day 21, the pressurized samples showed the best textural properties. Peaches subjected to HPP + VP also had significantly lower content of ethanol and PPO activity than the other treatments, which evidences that fermentation and browning were successfully inhibited by this combination. It can be concluded that HPP + VP could preserve fresh-cut peaches for at least 21 days at 10 °C, with only a slight translucency caused by VP.